Produksi Dan Formulasi Surfaktan Berbasis Metil Ester Sulfonat Dari Minyak Biji Karet Untuk Aplikasi Enhanched Oil Recovery (Eor) (Studi Kasus : Lapangan Karbonat, Prabumulih, Sum-Sel) - Hersa Rizki Rahmatullah (Politeknik Akamigas Palembang, 2017)
One of the ways in improving oil recovery from a reservoir is by injecting surfactant. The use of surfactant is intended to decrease the interfacial tension between oil and water in order to bring the oil out of the pore stones of the reservoir. It is a good chance to develop the kind of vegetable oil based surfactant which is from rubber seed oil. According to the data of the Directorate General of Plantation year 2013, Indonesia is one of the countries which have the largest rubber plantation in the world. Yet, rubber seed is wasted so far. Rubber seed contains vegetable oil which can be developed into methyl ester sulfonate based surfactant (MES). Due to the carbonate formation that will be tested, hence, the best formulation of MES based surfactant for Enhanced Oil Recovery (EOR) application in this formation is a formula with MES based surfactant composition of 0.3%, Na2CO3 0.3% and salinity 15.000 ppm. In this particular study, surfactant formula is added into carbonate reservoir sample taken from Prabumulih by creating concentration from surfactant formula and reservoir sample as much as 5%, 10%, 15% and blank. The best MES based surfactant formula to be applied on oil industry of carbonate field is the surfactant formula with 15% dosage composition.